2003
DOI: 10.1084/jem.20021980
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Prion Protein PromotesBrucellaInfection into Macrophages

Abstract: The products of the Brucella abortus virB gene locus, which are highly similar to conjugative DNA transfer system, enable the bacterium to replicate within macrophage vacuoles. The replicative phagosome is thought to be established by the interaction of a substrate of the VirB complex with macrophages, although the substrate and its host cellular target have not yet been identified. We report here that Hsp60, a member of the GroEL family of chaperonins, of B. abortus is capable of interacting directly or indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
103
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 57 publications
(73 reference statements)
4
103
1
2
Order By: Relevance
“…Possible host cell surface receptors for Brucella have been recently identified [8][9][10], but the role of cellular prion protein in Brucella uptake remains questionable [11]. Brucella virulence factors involved in bacterial invasion have not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Possible host cell surface receptors for Brucella have been recently identified [8][9][10], but the role of cellular prion protein in Brucella uptake remains questionable [11]. Brucella virulence factors involved in bacterial invasion have not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Neither virulence factors that allow intracellular survival of Brucella species nor the specific factors that induce such virulence have been elucidated. B. abortus is internalized by macrophages by swimming on the cell surface with generalized membrane ruffling for several minutes, a process termed 'swimming internalization', after which the bacteria are enclosed by macropinosomes (Watarai et al, 2002a).Recently we showed that Hsp60, a member of the GroEL family of chaperonins, of B. abortus is secreted on the bacterial surface through a type IV system and can interact with the cellular prion protein (PrP G ) on macrophages (Watarai et al, 2003 vacuoles rapidly fuse with early autophagosomes that acquire vacuolar H + -ATPase and lysosome-associated membrane proteins (LAMPs), mature into late autophagosomes, inhibit fusion with lysosomes and finally become replicating vacuoles, normally associated with the endoplasmic reticulum (Comerci et al, 2001; Pizarro-Cerda et al, 1998a, b). The genetic basis of B.abortus virulence is still poorly understood.…”
mentioning
confidence: 99%
“…The sub-bacteriostatic and sublethal concentrations of chloramphenicol were 1 and 25 mg ml 21 , respectively. Bacterial suspensions were incubated in a shaker at 37 uC for 9 h; the resulting cultured bacteria were heat-fixed, Gram stained and observed by phase-contrast or bright-field microscopy (Olympus; magnification 61000).Bacterial morphology within macrophages was assessed by using a modification of the method of Kim et al (2003). Infected macrophages were fixed in 4 % periodate/lysine/paraformaldehyde/sucrose for 1 h at 37 uC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Entry is mediated by surface-exposed bacterial and host membrane complexes at cholesteroland glycosylphosphoinositide (GPI)-rich hostcell membrane domains (lipid rafts) (PizarroCerda et al 1998;Watarai et al 2002Watarai et al , 2003Kim et al 2004;Nakato et al 2012) in a phosphoinositide (PI)-3 kinase, actin, ezrin, Rho, Rac, Cdc42, and/or Toll-like receptor (TLR)4-dependent manner (Fig. 2) (Guzman-Verri et al 2001;Chaves-Olarte et al 2002;Watanabe et al 2009).…”
Section: Uptake Of Brucella In Bcvsmentioning
confidence: 99%